Of languages and epistemologies: Reflections of a graduate international student on the road to becoming a researcher - Colombo, Laura Marina (2014)
This reflection piece is based on my experience as an international student in the U.S. I invite the reader to join me in re-visiting my road to becoming a researcher to unveil the challenges and advantages that I found being between different languages and epistemologies.